Chineseness and behavioural complexity: rethinking Chinese tourist gaze studies. Issue 3 (22nd August 2021) - Li, Mohan; Tucker, Hazel; Chen, Ganghua
Abstract : Purpose: This study aims to reconsider Chinese tourist gaze studies, examining the extent to which extant studies and theoretical models relating to the Chinese tourist gaze have overcome the Eurocentric limits of John Urry's concept of the tourist gaze and elaborated the complexity of Chinese tourists' gazes and visual practices. Design/methodology/approach: Content analysis is carried out, examining research articles, books, book chapters and PhD and MSc theses collected from multiple English and Chinese databases. Findings: The research results manifest that, overall, the previous studies, mobilise cultural essentialism, with an overestimation of the "Chineseness" of Chinese tourists' behavioural patterns, which are widely believed to be framed by, but also constituting of, unique Chinese culture. Overdependence on Chinese cultural values and traditional philosophies as sources for rationale has resulted in a handful of theoretical frameworks, which appear to be of insufficient magnitude both in terms of their contribution to the original tourist gaze model and in their manifesting of the complexity of Chinese tourists' visual behaviour. Indeed the divide that once deliberately set apart West and East, or more precisely Western and Chinese tourist gazes, seems to become accentuated in most attempts to study and write about Chinese tourist gaze(s). The previous studies thus largely serve to mirror the Eurocentrism of Urry's gaze, rather than challenging it. Research limitations/implications: This study has a few limitations, especially, as this study only reviews and analyses the studies of the Chinese tourist gaze. It means that the conclusion might not well be generalised to either the investigation of the tourist gaze in another culture or the Chinese tourist studies, at large, which might exhibit a different pattern deserving more academic attention in future. Moreover, the authors recommend the future researchers, who are eager to probe Chinese tourists' behavioural pattern, to seek for new pathways and alternative paradigms, which would be useful in overcoming the limits of cultural representations and in reducing the problematic Sino-Western divide. Originality/value: Despite not aiming to reconceptualise the Chinese tourist gaze, this review paper contributes to the field of tourist gaze studies by engaging critically with the bias and theoretical insufficiencies that have emerged, while this concept is appropriated and re-formulated to explain Chinese tourists' gazes and visual practices. On this basis, the authors suggest a critical redirection of the extant Chinese tourist gaze studies, which would be rather significant to those researchers in future with an interest to research what the Chinese tourists prefer to see in travel and how they engage with the gazee. Abstract : 中国性与行为复杂性：反思中国游客凝视研究 目的: 本文重新检视有关中国游客凝视的研究, 审视现有研究和理论模型在多大程度上克服了约翰·厄里提出的游客凝视概念所蕴含的欧洲中心主义的局限, 并阐述中国游客凝视和视觉实践的复杂性。 设计/方法/进路: 本研究进行了内容分析; 资料来源于多个渠道的期刊论文、书籍、书章和博硕论文。 发现: 总体而言, 以往研究调动了文化本质主义, 过分强调了中国游客行为模式的"中国性"–被广泛认为受制于中国文化, 且也是中国文化一部分。对作为基本理论来源的中国文化价值观和传统哲学的过度依赖产生了一系列理论框架, 但它们在对最初的游客凝视模型的贡献上, 以及在对中国游客视觉行为的复杂性的阐释上, 都是不够的。在大部分中国游客凝视研究中, 以往对西方游客和中国游客的凝视的刻意区分都得以凸显, 从而映照出厄里的游客凝视概念所蕴含的欧洲中心主义。 原创性/价值: 虽然本评述论文并不致力于对中国游客凝视进行重新概念化, 但依旧对游客凝视研究领域做出了贡献。当游客凝视这一概念被挪用且重新定制以解释中国游客凝视和视觉实践时, 本文对涌现其间的偏见和理论上的缺陷进行了批判性的揭示。在此基础上, 我们认为, 有必要对有关中国游客凝视的研究做出批判性的重新定向。这对于未来有志于研究中国游客视觉偏好以及他们如何与被凝视者互动的研究人员而言, 尤其重要。 启示局限/启示: 本研究有一些局限, 特别是, 因为我们只评价和分析了有关中国游客凝视的研究。这意味着, 我们的结论可能不能被推广至对其他文化情境下的游客凝视的调查, 也不能推广至中国游客研究整体。我们建议, 对中国游客行为模式感兴趣的研究人员需要寻求新的路径和替代性的范式, 以克服文化表象的局限并减少中西分歧带来的问题。 Abstract : Carácter chino y la complejidad de comportamiento: repensar los estudios de la mirada del turista chino Objetivo: Este artículo reconsidera los estudios de la mirada del turista chino para investigar hasta qué punto los estudios y los modelos teóricos existentes sobre la mirada del turista chino han superado los límites eurocéntricos del concepto de la mirada del turista de John Urry y explicado la complejidad de la mirada del turista chino y las prácticas visuales. Diseño/metodología/método: Se lleva a cabo el análisis de contenido investigando artículos de investigación, libros, capítulos de libros y las tesis de PhD y de MSc provenientes de las diversas bases de datos tanto en inglés como en chino. Hallazgos: Los resultados de la investigación manifiestan que, en general, los estudios anteriores movilizan el esencialismo cultural con una sobrestimación del "carácter chino" del modelo del comportamiento de turistas chinos, se cree en gran medida que el cual es motivado por la cultura china mientras forma parte de ella. Lo que la fuente de los fundamentos básicos sobredepende de los valores culturales y la filosofía tradicional de China resulta una pequeña cantidad de marcos teóricos, que no son suficientes tanto para la contribución al modelo original de la mirada del turismo como para manifestar la complejidad del comportamiento visual de turistas chinos. De hecho, se destaca la intención de la separación del Occidente y el Oriente, o hablando de forma precisa, de la mirada del turista occidental y la del turista chino al estudiar y escribir sobre la mirada del turista chino. Los estudios anteriores reflejan el eurocentrismo de la mirada de Urry en vez de ponerlo en duda. Originalidad/valor: A pesar de que el artículo no tiene la reconceptualización de la mirada del turista chino como su objetivo, contribuye al ámbito de la investigación de la mirada del turista a través de revelar de manera crítica el prejuicio y la insuficiencia teórica que ya ha existido cuando se usa y se reformula este concepto para explicar la mirada del turista chino y las prácticas visuales. Con lo que hemos mencionado, planteamos una redirección crítica de los estudios existentes de la mirada del turista chino, lo cual sería significativo para aquellos que tienen la intención de investigar qué prefieren ver los turistas chinos durante el viaje y cómo van a interactuar con los mirados en el futuro. Límites de investigación/inferencia: Esta investigación tiene varios límites, sobre todo, como solo revisamos y analizamos los estudios de la mirada del turista chino, lo cual significa que nuestra conclusión no se podría generalizar tanto a la investigación de la mirada del turista de otras culturas como a los estudios del turismo chino, que mostrarían un modelo diferente que merece más atención académica en el futuro. Al mismo tiempo, recomendamos a las personas que se interesen por investigar el modelo del comportamiento de los turistas chinos buscar nuevos caminos y paradigmas alternativos, los cuales serían útiles para superar los límites de las representaciones culturales y reducir la división problemática sino-occidental.